Public’s sentiment on COVID-19 nurses survivor - Asti Melani Astari; Whaisna Switaningtyas; Yati Sri Hayati (Intelektual Pustaka Media Utama, 2022)
Nurse plays a critical role in health services during the coronavirus disease 2019 (COVID-19) pandemic. Their duties and responsibilities impose them to stay around the patients with a high probability to become the spreaders of the virus. This study explored the experience of nurses about the public’s sentiment when the nurses confirmed COVID-19. This qualitative research was performed using a phenomenological approach. The data were collected through direct in-depth interviews and then analyzed using the Colaizzi method with a seven-step approach to 12 participants. The results showed: i) feeling stigmatized by the community and ii) feeling that the social stigma has an impact on the family, both of which are composed of several sub-themes and categories. Participants found a lot of experiences and challenges because they had to carry out their responsibilities in an environment enforcing them at risk of contracting the virus. Participants who had ever been confirmed positive for the COVID-19 perceived the stigma and negative views by the community. They needed support from all parties to create a good atmosphere and correct the wrong information related to the treatment of patients with COVID-19. Families and communities should provide motivation for the confirmed COVID-19 nurses to recover and complete the isolation procedure.